2021
DOI: 10.1021/jacs.1c10600
|View full text |Cite
|
Sign up to set email alerts
|

Small Organic Molecule Based on Benzothiadiazole for Electrocatalytic Hydrogen Production

Abstract: A small organic molecule 2,1,3-benzothiadiazole-4, 7-dicarbonitrile (BTDN) is assessed for electrocatalytic hydrogen evolution on glassy carbon electrode and shows a hydrogen production Faradaic efficiency of 82% in the presence of salicylic acid. The key catalytic intermediates of reduced species BTDN –• and protonated intermediates are characterized or hypothesized by using various spectroscopic methods and density functional theory (DFT)-based calculations. With the experimental and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…More importantly, the shift of the peak as a result of two-electron reduction is greater than the shift as a result of one-electron reduction. The lower shift of the peak induced by reduction of BTZ derivatives in FTIR measurement was also reported by Axelsson et al, suggesting that it was caused from delocalization of the radical in BTZ . Besides, they mentioned that two-electron reduction of the BTZ derivative in combination with a proton was plausible through disproportionation reactions .…”
Section: Resultssupporting
confidence: 63%
“…More importantly, the shift of the peak as a result of two-electron reduction is greater than the shift as a result of one-electron reduction. The lower shift of the peak induced by reduction of BTZ derivatives in FTIR measurement was also reported by Axelsson et al, suggesting that it was caused from delocalization of the radical in BTZ . Besides, they mentioned that two-electron reduction of the BTZ derivative in combination with a proton was plausible through disproportionation reactions .…”
Section: Resultssupporting
confidence: 63%
“…can work as an electrocatalyst for hydrogen evolution. 114 The mechanism was mainly studied using electrochemical methods, where cyclic voltammetry was used to identify specific reductions and protonation events and bulk electrolysis could confirm catalytic hydrogen evolution. The catalytic intermediates were characterised using spectro-electrochemical methods to capture spectra of the intermediates in both UV-vis and IR.…”
Section: Electron Transport To the Cocatalyst (Step 3)mentioning
confidence: 99%
“…Based on these calculations, the fluorine substituents may have considerable effects on stabilizing the transition state, thus leading to more efficient proton adsorption to the N site of BT. [45,66] In addition, Woods et al reported that the higher relative dielectric permittivity of conjugated polymer causes the adsorption of water, stabilizing the photogenerated charge carriers. [22] Collectively, we demonstrated that the increased permittivity of P3 would decrease the transition potential for proton reduction reaction, predicted by DFT.…”
Section: Resultsmentioning
confidence: 99%